2003
DOI: 10.1038/sj.bmt.1704316
|View full text |Cite
|
Sign up to set email alerts
|

Drug interactions in the hematopoietic stem cell transplant (HSCT) recipient: what every transplanter needs to know

Abstract: Summary:Pharmacokinetic drug interactions among hematopoietic stem cell transplant recipients can result in either increases in serum concentrations of medications, which may lead to enhanced toxicity; or reduced serum concentrations, which can lead to treatment failure and the emergence of post transplant complications. The use of drugs that have a narrow therapeutic index, such as cyclosporine/tacrolimus (calcineurin inhibitors), increases the significance of these interactions when they occur. This report w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 121 publications
1
42
0
Order By: Relevance
“…Tacrolimus is a substrate of an efflux transporter, Pglycoprotein (P-gp), and is metabolized by cytochrome P450 3A4 (CYP3A4) (22). Thus there is a possibility that tacrolimus causes drug interactions with other drugs that are also substrates of P-gp or CYP3A4 (23). In this study, we confirmed that the rate of absorption and/or clearance of s.c. administered h-IFN were not affected by i.v.…”
Section: Discussionsupporting
confidence: 91%
“…Tacrolimus is a substrate of an efflux transporter, Pglycoprotein (P-gp), and is metabolized by cytochrome P450 3A4 (CYP3A4) (22). Thus there is a possibility that tacrolimus causes drug interactions with other drugs that are also substrates of P-gp or CYP3A4 (23). In this study, we confirmed that the rate of absorption and/or clearance of s.c. administered h-IFN were not affected by i.v.…”
Section: Discussionsupporting
confidence: 91%
“…Patients in a conditioning regimen with cyclophosphamide and cyclosporine require more frequent monitoring of cyclosporine blood levels in order to avoid the risk of acute GVHD [7,14]. Cyclosporine was the only immunosuppressant prescribed to the patients investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…79 The role of genetic polymorphisms in the cytochrome P-450 enzyme system in the liver in transplant toxicity has not been sufficiently explored. 80,81 Larger cohort studies are needed to confirm the associations that have been observed between specific genetic variants and HSCT-related complications and to identify other genes that modify risk. The benefits of these studies to patients are obvious: the potential for improved risk stratification and development of more effective interventions that target high-risk individuals.…”
Section: Future Directionsmentioning
confidence: 99%